Regulation of Smoothened Trafficking and Abundance in Hedgehog Signaling - Jia, Jianhang; Jiang, Jin (Frontiers in Cell and Developmental Biology, 2022)
The GPCR-family protein Smoothened (Smo) is essential for Hedgehog (Hh) signal transduction in both insects and vertebrates. The regulation of subcellular localization and abundance of Smo is a critical step in Hh signaling. Recent studies have demonstrated that Smo is subjected to ubiquitination mediated by multiple E3 ubiquitin ligases, leading to Smo endocytosis and subsequent degradation through the proteasome- and lysosome-mediated pathways in Drosophila. Ubiquitination of Smo also promotes its ciliary exit in mammalian cells. Hh inhibits Smo ubiquitination by blocking E3 ligase recruitment and promoting Smo deubiquitination through the ubiquitin-specific protease 8 (USP8) in Drosophila. Inhibition of Smo ubiquitination by Hh promotes Smo cell surface accumulation in Drosophila and ciliary accumulation in mammalian cells. Interestingly, Hh also induces sumoylation of Smo in both Drosophila and mammalian cells, which promotes Smo cell surface/ciliary accumulation. This review focuses on how ubiquitination and sumoylation regulate Smo intracellular trafficking and abundance and how these processes are regulated by Hh.